Imunoexpressão de fatores reguladores da osteoclastogênese na doença periodontal em humanos e sua relação com os parâmetros clínicos - Amaral, Bruna Aguiar do (2011)
Periodontal disease is an infection initiated by oral periodontal pathogens that trigger an immune response culminating in tissue destruction. This destruction is mediated by the host by inducing the production and activation of lytic enzymes, cytokines and the stimulation of osteoclastogenesis. The aim of this study was to compare the immunohistochemical expression of factors involved in bone resorption, RANKL (Ligand Receptor Activator of Nuclear Factor kappa B), OPG (Osteoprotegerin) and TNF-α (tumor necrosis factor alpha) between the gingival healthy, gingivitis and chronic periodontitis and correlate them with clinical parameters. The sample consisted of 83 cases and 12 clinically healthy gums, 42 gingivitis and 29 periodontitis, from 74 adolescent and adult patients with a mean age of 35 years, without systemic changes and non-smokers, predominantly female and race brown. There was no statistically significant difference for the expression of anti-RANKL (p = 0.581) and RANKL / OPG ratio (p = 0.334) when comparing the three conditions, but the anti-OPG and anti-TNF-α showed statistically significant between the types of injury (p = 0.001 and p <0.001, respectively), showing greatest expression in periodontitis. In cases of periodontitis, the variable clinical attachment loss (PIC) was statistically significant and positive correlation, respectively, with immunostaining of anti-RANKL (p = 0.002, p = 0.001 and r = 0.642), anti-OPG (p = 0.018, p = 0.014 and r = 0.451), anti-TNF-α (p = 0.032, p = 0.014 and r = 0.453) and the percentage ratio of RANKL / OPG (p = 0.018, p = 0.002 and r = 0.544). The tooth mobility (MB) showed a statistically significant difference only with immunohistochemical anti-RANKL (p = 0.026), and probing depth (PD) was positively correlated with anti-RANKL (p = 0.028 and r = 0.409), both in cases of periodontitis. Only in cases of gingivitis TNF-α was positively correlated with RANKL (p = 0.012 and r = 0.384) and the RANKL / OPG ratio (p = 0.027 and r = 0.341). Given these results, we conclude that the greatest expression of TNF-α in periodontitis demonstrates a relationship with the progression and severity of periodontal disease and the correlation between all antibodies and clinical attachment loss demonstrates their involvement in periodontal bone resorption